2019
DOI: 10.18585/inabj.v11i2.517
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tomato Juice in Increasing Ki-67 Expression and Epithelial Thickness on The Vaginal Wall of Menopausal Rats

Abstract: BACKGROUND: Dyspareunia and pain due to the decrease of vaginal wall thickness usually happen in menopausal women. The reduction of estrogen levels cause the decreasing of cell proliferation and the thinning of vaginal wall epithelium. Tomato (Solanum lycopersicum) is a source of phytoestrogens, which produce estrogenic effects. This study aims to assess the effect of tomato juice on Ki-67 expression and epithelial thickness of the vaginal wall in menopausal rats.METHODS: This was an experimental study using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…This condition is not favorable for the growth of vaginal microbiota, especially vaginal Lactobacilli. (16,27) This finding is in line with a study that found L. crispatus was dominant in healthy vaginal conditions. (10) This finding is also similar to a previous study that found a low proportion of Lactobacillus sp.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This condition is not favorable for the growth of vaginal microbiota, especially vaginal Lactobacilli. (16,27) This finding is in line with a study that found L. crispatus was dominant in healthy vaginal conditions. (10) This finding is also similar to a previous study that found a low proportion of Lactobacillus sp.…”
Section: Discussionsupporting
confidence: 90%
“…Some menopausal women complain about the burning sensation in the vulva, and at least 50% of postmenopausal women experience urogenital tract changes associated with VVA. (11)(12)(13)(14)(15)(16) Decrease in estrogen levels during menopause affect the female urogenital tract. (17) During menopause, the proliferation of epithelial cells is reduced, causing the thinning of vaginal mucosal epithelium, atopy of vaginal wall, and parabasal cell dominance in the epithelial layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Several studies on phytoestrogen, as natural estrogens derived from plants, have been carried out to treat menopausal symptoms. 6 The phytoestrogen can induce the proliferation and maturation of the epithelium on the vaginal surface, which plays an important role in the vagina's defence against pathogenic bacteria. 6,7 Loss of estrogen production from the ovaries causes menopausal women to experience symptoms of atrophic vaginitis.…”
Section: Introductionmentioning
confidence: 99%
“…6 The phytoestrogen can induce the proliferation and maturation of the epithelium on the vaginal surface, which plays an important role in the vagina's defence against pathogenic bacteria. 6,7 Loss of estrogen production from the ovaries causes menopausal women to experience symptoms of atrophic vaginitis. 8 Estrogen defi ciency results in changes in epithelial cell maturation so that the glycogen content will decrease.…”
Section: Introductionmentioning
confidence: 99%